2021
DOI: 10.5788/31-1-1645
|View full text |Cite
|
Sign up to set email alerts
|

Use of Dictionaries and Online Tools for Reading by Thai EFL Learners in a Naturalistic Setting

Abstract: Dictionaries and online tools are regarded as important tools for finding out the meanings of unknown words or checking the usage of interesting words. This study investigated students' use of dictionaries and online tools in a natural setting by identifying the type of words they look up in their dictionaries and the types of dictionaries they use for the look-up. Fourteen learners from a Thai public university participated as the subjects by filling in a task record form which included the names of the dicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…In terms of vocabulary, Alhaisoni (2020) reported that Saudi students do not necessarily retain the words they look up in English-to-Arabic dictionaries, both because (a) they do not spend enough time on entries and read all the meanings, and (b) using English-to-English dictionaries is a better way of acquiring new vocabulary. Boonmoh (2021) reached similar conclusions in a study of Thai learners of English, in which students were observed to use dictionaries in an instrumentalist and superficial way, that is, as a rapid means of completing a given academic task, such as a writing task, rather than as part of a more holistic process of language learning. Students often believe that such usage of the dictionary is useful, but teachers disagree, finding that interactive feedback and other methods are better than dictionary usage for skill acquisition (Liu & Wu, 2019).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In terms of vocabulary, Alhaisoni (2020) reported that Saudi students do not necessarily retain the words they look up in English-to-Arabic dictionaries, both because (a) they do not spend enough time on entries and read all the meanings, and (b) using English-to-English dictionaries is a better way of acquiring new vocabulary. Boonmoh (2021) reached similar conclusions in a study of Thai learners of English, in which students were observed to use dictionaries in an instrumentalist and superficial way, that is, as a rapid means of completing a given academic task, such as a writing task, rather than as part of a more holistic process of language learning. Students often believe that such usage of the dictionary is useful, but teachers disagree, finding that interactive feedback and other methods are better than dictionary usage for skill acquisition (Liu & Wu, 2019).…”
Section: Discussionsupporting
confidence: 60%
“…EFL literature has a number of focuses when it comes to discussing dictionary use. One positive interpretation is that dictionaries help students acquire new vocabulary, improve spelling, and develop their writing quality (Abbasi et al, 2019;Alhaisoni, 2020;Boonmoh, 2021;El-Sawy, 2019;Pyo, 2020;Zhang et al, 2021). This interpretation is generally positive in its assessment of how dictionaries are useful to EFL students.…”
Section: Literature Reviewmentioning
confidence: 99%